2021
DOI: 10.31662/jmaj.2021-0090
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Ciliogenesis

Abstract: Autophagy is a major intracellular degradation system and plays important roles in various physiological processes such as metabolic adaptation and intracellular homeostasis. It degrades intracellular components both randomly and selectively. Autophagic activity is tightly regulated primarily by nutrient availability, but also by other extracellular and intracellular signals. Growing evidence suggests that there are multiple links between autophagy and the primary cilium. The primary cilium is an organelle pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…The present study then investigated the possible mechanisms responsible for the enhanced autophagy and mitophagy induced by icariin. Previous studies have demonstrated that TFEB regulates the biogenesis of both autophagosomes and lysosomes (Settembre et al, 2011; Yamamoto & Mizushima, 2021). As shown in Figure 3a, the location of the nucleus and cytoskeleton was determined by staining with DAPI and phalloidin; the fluorescence staining of TFEB revealed a significantly higher rate of nucleation in the icariin‐treated cells (Figure 3b).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The present study then investigated the possible mechanisms responsible for the enhanced autophagy and mitophagy induced by icariin. Previous studies have demonstrated that TFEB regulates the biogenesis of both autophagosomes and lysosomes (Settembre et al, 2011; Yamamoto & Mizushima, 2021). As shown in Figure 3a, the location of the nucleus and cytoskeleton was determined by staining with DAPI and phalloidin; the fluorescence staining of TFEB revealed a significantly higher rate of nucleation in the icariin‐treated cells (Figure 3b).…”
Section: Resultsmentioning
confidence: 98%
“…The process of autophagy is divided into four parts, namely the formation of the phagophore, the formation of autophagosomes, the formation of lysosomes, and the fusion and degradation of the autophagosome–lysosome complex (Yamamoto & Mizushima, 2021). As demonstrated in Figure 4a, icariin notably promoted the expression levels of TFEB/Lamin B1 and LC3II/I in the cells exposed to xo‐LDL.…”
Section: Resultsmentioning
confidence: 99%
“…Because inhibiting ciliogenesis reduces lysosomal protein degradation, impaired autophagy may underlie the obesity phenotype ( Lee et al, 2020 ). When autophagy is disrupted in POMC neurons, axon growth is impaired, and adiposity subsequently develops ( Coupé et al, 2012 )– indicating a bidirectional relationship between ciliogenesis and autophagy regulation ( Yamamoto and Mizushima, 2021 ). High-fat diets, specifically enriched with palmitic acid blunts autophagy by increasing levels of SQSTM1 and reducing the transformation of LC3I-LC3II in POMC neurons.…”
Section: Primary Cilia Integrate Peripheral Signals At Hypothalamic C...mentioning
confidence: 99%
“…Autophagy is an intracellular degradation process that plays an important role in maintaining intracellular homeostasis. Ciliogenesis and autophagy share several commons as they both show dual roles in tumorigenesis and could be triggered by nutrient starvation (Yamamoto & Mizushima, 2021). Based on this, recent studies have focused on the crosstalk between these two processes.…”
Section: Primary Cilia Autophagy and Cell Deathmentioning
confidence: 99%